The Effectiveness of Digital Storytelling for Young Learners' Vocabulary Mastery - Lailatul Maya; Muhammad Labib Al Halim (FKIP, Universitas Billfath Lamongan, 2021)
This research aimed to explore the effectiveness of using digital storytelling for young learners’ vocabulary mastery. Digital storytelling is the combination of spoken narrative, a number of digital picture, soundtrack, and technology to share stories. The subject of the research was 23 young learners in fifth grade at MI Mathlaul Ulum Ngadirejo. This research was a quantitative descriptive research in form of one-group pretest-posttest pre-experimental research design. The research instruments were pre-test and post-test evaluations. The findings of the research presented the significant improvement of young learners’ mean score of pre-test and post-test. The mean score of post-test (72,9) was higher than the mean score of pre-test (52,3). From the result, it proved that there was a significant effect of the implementation digital storytelling on young learners’ vocabulary mastery.